OPTIMIZATION AND RESEARCH OF TIDAL TURBINE BLADES BASED ON GENETIC ALGORITHM - WANG YongDing; LI NingYe (Jixie qiangdu)
Improving the efficiency of tidal turbine is the key research of oceanenergy development. The focus of improving the efficiency of tidal turbine lies in the geometry of the turbine blades. Based on the hydrofoil of NACA4412,the method of Joukowski conformal transformation was used to build the parameterized model,the genetic algorithm was realized by MATLAB programming and an optimal solution was found on the basis of using high lift-drag ratio as the objective function under the design variables and constrains. After obtain the optimal solution,use the CFD software was used to simulate the initial hydrofoil and the optimized laminar hydrofoil. According to the results,we can find that the optimized hydrofoil hada great improvement in the liftdrag ratio and lift coefficient compared with the initial hydrofoil. The lift coefficient and the maximum lift-drag ratio of the hydrofoil are increased by 18. 72% and 46. 84% respectively,and the angle of attack is smaller when the hydrofoil reaches the maximum lift-drag ratio after being optimized. The results validate the rationality and validity of the proposed optimal solution and provide a theoretical basis for the subsequent optimization design of tidal turbine hydrofoils.